Risk of retinal tear or detachment with oral fluoroquinolone use: a cohort study - Eftekhari, Kian (2014)
PURPOSE: To determine if oral fluoroquinolone exposure is associated with an increased hazard for having a retinal tear or detachment. METHODS: A retrospective cohort study was performed using individuals who met inclusion criteria from The Health Improvement Network (THIN) database. Cohorts were created for individuals who had a prescription written for either an oral fluoroquinolone or an oral β-lactam antibiotic (comparison group). Subjects were excluded if they had a previous diagnosis of a retinal tear or detachment (hereafter retinal break, or RB) or a procedure code to treat an RB, were in the practice for less than 365 days, had a previous prescription for either antibiotic within 365 days of the index date, or had intraocular surgery or a diagnosis of endophthalmitis within 90 days prior to the antibiotic prescription. Covariates of interest were age, gender, diabetes and year of index. The primary outcome measure of interest was the hazard ratio of undergoing a procedure to treat a RB within 7, 30, 90 or 365 days after exposure to an oral fluoroquinolone prescription versus an oral β-lactam prescription. RESULTS: After exclusions, 6,604,423 prescriptions (290,393 fluoroquinolone; 6,314,030 β-lactam) from 3,413,498 patients (247,073 fluoroquinolone; 3,303,641 β-lactam) and, 2,685 RB procedures were eligible for analysis (661 retinal tears, 2,024 retinal detachments). For fluoroquinolones, zero, one, five, and 23 retinal breaks occurred at the 7-, 30-, 90-, and 365-day time points, respectively. For β-lactam prescriptions, 7, 28, 87, 373 retinal breaks occurred at the 7-, 30-, 90-, and 365-day time points, respectively. Due to zero events occurring in the fluoroquinolone cohort during the 7-day observation period an unadjusted or an adjusted hazard ratio (and subsequent p-value or confidence intervals) were unable to be calculated. Univariate and multivariate analysis demonstrated that fluoroquinolones were not significantly associated with RB in the 30-, 90- or 365-day observation periods (30-day HR=0.78, p=0.80, 95% CI: 0 .11, 5.71; 90-day HR=1.25, p=0.63, 95% CI: 0.51, 3.08; 365-day HR= 1.35, p=0.16, 95% CI: 0.89 2.06). CONCLUSIONS: Our results do not support an association between oral fluoroquinolone use and subsequent procedures to treat a retinal break.